Assessment main of the oil and gas source properties of the jurassic rocks of the tersko-caspian foredeep - Anatoly Andreevich Yaroshenko; Anna Aleksandrovna Paporotnaya; Julia Andreevna Savina; Olesia Vladimirovna Skripnyuk (Наука. Инновации. Технологии)
The study of the organic matter (OM) of rocks of the deposits of the Tersko-Caspian foredeep (TCF) on the basis of luminescent and chemical-bituminous analyzes was carried out. The increased content and geochemical characteristics of the dispersed organic matter (DOM) of the Middle Jurassic terrigenous complex within the studied territory make it possible to classify these deposits as oil and gas source rocks. According to the elemental composition of the chloroform components of OM using the Van Crevelen diagram, two genetic types of OM are identified: sapropelic and humus-sapropelic. The features of the lithological composition of the Upper Jurassic rocks, the low content of DOM associated with sedimentation conditions, do not allow considering these deposits as a petroleum complex in the context of Jurassic deposits. The conducted of the Jurassic complex rocks allow to assume the possibility of discovery of new accumulations of oil and gas in the presence of resources - reservoirs and traps for HC deposits. In order to search for reservoir scientists and local uplifts, it is necessary to carry out analytical studies, seismogeo-logical modeling and the formation of a detailed volumetric model of the geological environment based on deep seismic 2D cuts and well log data.